Taking into account type I and II errors of switching device for system with hot redundancy - Москвіна, Ірина Ігорівна; Стефанович, Тетяна Олександрівна; Щербовських, Сергій Володимирович (Technology audit and production reserves, 2015)
One of the ways to improve the reliability of technical systems is the use of hot redundancy. Switching between the main and reserve elements makes switching device. When analyzing the reliability of such systems it is important to consider the impact of switching device on the reliability of the system. This influence is evident in the mistakes of the first and second kind that is the wrong switch or switching time of admission. Both errors reduce reliability of the system and lead to underutilization of resources. It is proposed a model of reliability of duplicated system with hot redundancy and imperfect switching device to determine the likelihood of its success. The peculiarity of the model is that it adequately takes into account type I and II errors for the switching device. Reliability of the system is described mathematically by the k-terminal dynamic fault tree, and the probability determined by the characteristics of homogeneous Markov model. It is quantitatively shown how increasing options that meet these errors, reduces the probability of failure of the system.